The Relationship Of Online Games With The Disciplinary Character Of Elementary School Students: The Relationship Of Online Games With The Disciplinary Character Of Elementary School Students - Helmaniah, Shendi; Nuroh, Ermawati Zulikhatin (Universitas Muhammadiyah Sidoarjo, 2023)
This quantitative descriptive research investigates the intensity of online gaming among Grade V students at SD Negeri 4 Bandungrejo, Bantur District, Malang Regency, aiming to assess its relationship with students' disciplinary character. Data was collected using questionnaires and documentation from a sample of 8 students, and analyzed through descriptive statistical methods. The findings reveal a negative and insignificant correlation between online gaming and students' disciplinary character, indicating that online gaming might not significantly influence their discipline. This study provides valuable insights for educators, parents, and policymakers on understanding and addressing potential challenges related to online gaming and its impact on students' behavior. Highlights: Importance of Disciplinary Character: This research focuses on assessing the disciplinary character of Grade V students in relation to their engagement in online gaming, shedding light on its significance for their overall development. Quantitative Descriptive Approach: The study employs a quantitative research design to provide an overview of the intensity of online gaming among Grade V students, allowing for objective data analysis and inference. Correlational Analysis: By utilizing a correlative model, the research examines the relationship between online gaming and students' discipline, presenting insights into any potential connections or lack thereof. Keywords: Online gaming, Grade V students, Discipline, Quantitative research, Correlational analysis.